Tungku Sekam Sebagai Bahan Bakar Alternatif Pada Sterilasasi Media Jamur Tiram - Puspita, R. D.; Desna, Desna; Husin, A.D.; Irzaman, Irzaman; Darmasetiawan, H.; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Medium Sterilization which has been packaged in the baglog on the oyster mushroom cultivation, one of them can be done with a steam technique using the drum. Commonly used fuel is firewood that could be assisted by using coal or kerosene or LPG gas. Rice husk as alternative fuel of kerosene and firewood can be used as fuel for the medium sterilization. The husk which used in the sterilization process of oyster mushrooms medium for 6 hours, 8 hours, and 10 hours as much as 55.5 kg, 60 kg and 67 kg. The efficiency which obtained in the medium sterilization of oyster mushrooms with using rice husk is reached 45.23% in the medium sterilization for 8 hours. Â Keywords: Medium, oyster mushrooms, rice husk, sterilization